Kanon 573: Pedoman Autentik untuk Menghidupi Spiritualitas Pasionis - Valentino, Beno (Publisher STPKat, 2024)
Canon 573 of the Code of Canon Law provides valuable guidance for religious life, especially for those who follow Passionist spirituality. This spirituality, which focuses on the suffering and redemption of Christ, has deep meaning and provides direction for many individuals committed to lives of service and devotion. Canon 573, with its provisions, serves as a pillar that not only regulates the formal aspects of religious life but also enriches and deepens the spiritual experience of its followers. In this spiritual journey, Canon 573 emphasizes the importance of living in community, carrying out religious vows, and dedicating oneself fully to God and others. Through a deep understanding of Canon 573, followers of Passionist spirituality can find a strong foundation for living a life in harmony with the teachings of Christ. This article aims to dig deeper into how Canon 573 can be an authentic guide in living out Passionist spirituality. By exploring the principles contained in this canon, we can understand how they apply to everyday life, enrich the journey of faith, and form a solid community committed to Christian values.